2019
DOI: 10.1038/s41598-018-36867-2
|View full text |Cite
|
Sign up to set email alerts
|

Soil parameters, land use, and geographical distance drive soil bacterial communities along a European transect

Abstract: To better understand the relationship between soil bacterial communities, soil physicochemical properties, land use and geographical distance, we considered for the first time ever a European transect running from Sweden down to Portugal and from France to Slovenia. We investigated 71 sites based on their range of variation in soil properties (pH, texture and organic matter), climatic conditions (Atlantic, alpine, boreal, continental, Mediterranean) and land uses (arable, forest and grassland). 16S rRNA gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 68 publications
6
53
1
Order By: Relevance
“…This larger role of microenvironment versus stochastic factors has repeatedly been seen in soil communities, where soils with similar environmental characteristics have similar microbial communities regardless of geographic distance (Fierer and Jackson, 2006;Lauber et al, 2009;Xu et al, 2014;Lladó et al, 2018;Plassart et al, 2019). Interestingly, we see this same trend in the bacterial communities of the soil-dwelling salamanders sampled in this study.…”
Section: Community Diversity and Compositionsupporting
confidence: 83%
See 2 more Smart Citations
“…This larger role of microenvironment versus stochastic factors has repeatedly been seen in soil communities, where soils with similar environmental characteristics have similar microbial communities regardless of geographic distance (Fierer and Jackson, 2006;Lauber et al, 2009;Xu et al, 2014;Lladó et al, 2018;Plassart et al, 2019). Interestingly, we see this same trend in the bacterial communities of the soil-dwelling salamanders sampled in this study.…”
Section: Community Diversity and Compositionsupporting
confidence: 83%
“…An emerging approach to study how microbial communities respond to environmental differences at both local and regional spatial scales is analyzing the effects of land use change. Habitat destruction, intensification of agriculture, and urbanization all alter edaphic properties, with correlated effects on microbial community composition (Zhao and Guo, 2010;Suleiman et al, 2013;Hawkes and Keitt, 2015;Plassart et al, 2019). In particular, urbanization may markedly alter the physicochemical properties of soil, leading to changes in the abundance and taxa of soil microbes (Zhao and Guo, 2010;Xu et al, 2014;Reese et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterivores and eukaryvores were differentially influenced by three edaphic factors, i.e. pH, texture and organic carbon content (Figure 4), the very same major drivers of bacterial community structure at national and continental scales (Bahram et al, 2018;Karimi et al, 2018;Plassart et al, 2019).…”
Section: Opposite Responses Of Trophic Guilds In Forestmentioning
confidence: 99%
“…The fungi cultivation can be taken as one kind of land use. Land use was considered as a main driving factor of bacteria for multiple land uses (arable, forest, grasslands) 25 . Previous studies also showed that microbial indexes could be influenced by land-use in many scale [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%